1998
DOI: 10.1021/ie970240w
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Transport in Porous Media:  A Volume-Averaging Approach

Abstract: Volume-averaging methods are applied to develop expressions for the effective electrophoretic mobility and dispersion coefficients in porous media as functions of media structure and electrical field. Case 1 accounts for electrophoretic transport in a two-phase system where both phases may be electrically conductive and the medium is uncharged, and case 2 adds hydrodynamic pressure-driven flow to one of the two phases. The results for case 1 suggest that the electrical field induces dispersion and that the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
25
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 71 publications
2
25
0
Order By: Relevance
“…Additional criticism of these challenges to the basic assumptions of the OMRC model is given in the rebuttal by Tietz [15]. Using the method of volume averaging [16], Locke [17] has shown that when variations of the local electrical field due to the presence of the obstacles are properly accounted for, the left-hand side of Eq. (1) is valid for any spatially periodic and isotropic media containing non-conducting obstacles that do not have percolation limits.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Additional criticism of these challenges to the basic assumptions of the OMRC model is given in the rebuttal by Tietz [15]. Using the method of volume averaging [16], Locke [17] has shown that when variations of the local electrical field due to the presence of the obstacles are properly accounted for, the left-hand side of Eq. (1) is valid for any spatially periodic and isotropic media containing non-conducting obstacles that do not have percolation limits.…”
mentioning
confidence: 99%
“…This result would also be valid, therefore, for ordered media. Locke [17] found that the electrophoretic mobility in this type of porous media is given by where S 1 is a function of the local electrical field and geometry (see Eq. 53 and 55 of Locke [17]).…”
mentioning
confidence: 99%
See 3 more Smart Citations